Chironomidae (Diptera) of Croatia with notes on the diversity and distribution in various habitat types - Čerba, Dubravka; Koh, Miran; Ergović, Viktorija; Mihaljević, Zlatko; Milošević, Djuradj; Hamerlík, Ladislav (Zootaxa, 2020)
The family of non-biting midges (Diptera, Chironomidae) represent one of the most common and abundant group in freshwaters, inhabiting a wide variety of habitats and ecological niches. Although there is a long tradition of limnological research in Croatia, to date no extensive species list has been made for this insect family. Thus, we summarized the results of our research and reviewed published data on chironomid fauna of Croatia in various freshwater habitat types, including extreme ones, such as caves, peatbogs or marine littoral. A total of 239 species were recorded representing five subfamilies: Chironominae (125 species) Orthocladiinae (83 species), Tanypodinae (23 species), Diamesinae (6 species) and Prodiamesinae (2 species). The most frequent species were Cricotopus bicinctus, Dicrotendipes nervosus, Synorthocladius semivirens, each found in more than 20% of the studied localities. Ablabesmyia monilis and Procladius choreus represented the most frequent Tanypodinae species, recorded in more than 12% and 17% of the sites, respectively. The research of chironomid ecology, diversity and distribution continues, which will provide new data and information, but this first comprehensive checklist provides a good starting point for those studying Chironomidae or other freshwater Diptera, in Croatia and Europe.